Evidence in international arbitration: with case-study of arbitration law of Latvia - Niedrīte, Sanda (Riga Graduate School of Law, 2018)
Within globalization and rapid technological process, more and more merchants involve in international transactions and thus more and more international disputes arise. Arbitration is one of dispute settlement mechanisms. It is a private mechanism with the aim of putting the parties of the dispute first by imposing party autonomy principle as guiding principle of arbitration. Arbitration has many advantages that are accepted and recognized within international arbitration society. However, this work, besides exploring advantages and reasons behind choosing arbitration, focuses on evidence in international arbitration and what is more – admissible evidence under the Arbitration law of Latvia. The work is structured in three main sections - arbitration as alternative dispute settlement mechanism and its advantages, evidence in international arbitration and evidence under the Arbitration law of Latvia.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Procedural law::Arbitration; Arbitration law; Latvia; International arbitration